2019
DOI: 10.1002/hed.25799
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival with combining quantitative 18F‐FDG PET/CT and DW‐MRI parameters in sinonasal malignancies

Abstract: Background We aimed to establish the prognostic value of 18F‐fluoro‐deoxy‐glucose positron emission/CT (18F‐FDG PET/CT) and diffusion‐weighted (DW) MRI in determining overall survival (OS), progression‐free survival (PFS), and distant metastasis‐free survival (DMFS) of sinonasal malignancies. Methods Sixty‐eight patients with sinonasal cancer who underwent both pretreatment 18F‐FDG PET/CT scan and head‐neck MRI from January 2009 through August 2017 were retrospectively reviewed. Kaplan‐Meier survival analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…At time of diagnosis, lymph node metastases or DM were only present in the minority of cases, which is in line with previous studies 9,27 . Similar to other series, sinonasal melanoma and SCC were among the most frequent tumor entities 9,22,28,29 . Initial radiological staging of sinonasal tumors requires detailed information on local tumor extent, especially with regard to infiltration of the orbit and skull base.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…At time of diagnosis, lymph node metastases or DM were only present in the minority of cases, which is in line with previous studies 9,27 . Similar to other series, sinonasal melanoma and SCC were among the most frequent tumor entities 9,22,28,29 . Initial radiological staging of sinonasal tumors requires detailed information on local tumor extent, especially with regard to infiltration of the orbit and skull base.…”
Section: Discussionsupporting
confidence: 87%
“…9,27 Similar to other series, sinonasal melanoma and SCC were among the most frequent tumor entities. 9,22,28,29 Initial radiological staging of sinonasal tumors requires detailed information on local tumor extent, especially with regard to infiltration of the orbit and skull base. As represented in the AJCC cancer staging system, this information determines the T category and serves as a strong predictor of the 5-year diseasespecific survival.…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Review of initial T classification revealed locally advanced tumors in the vast majority of all subjects (120 of 152 patients ≥ cT3, 78.9%) and adenocarcinoma, sinonasal melanoma, and SCC to be the most frequent tumor entities. [26][27][28][29] We found a low rate of both, LN metastases and DM in the initial staging. 15 LN metastases were predominantly located in ipsilateral and contralateral LN levels I and II, which confirms previous findings.…”
Section: Main Findingsmentioning
confidence: 54%